Analyzing the EU Refugee Crisis: Humanity, Heritage and Responsibility to Protect - Hadfield, Amelia (2015)
2015 has shaken the EU to its core. Hard upon the heels of geopolitical upheavals in Ukraine, as well as internal battles to define both Eurozone and energy governance, the refugee crisis has prompted a sober reckoning of the EU’s competence and its humanity. With an increasing number of articles and Special Issues in Politics and Governance focusing upon key aspects of the EU as both a political actor, and a source of governance, our autumn 2015 editorial looks briefly at the significance of the refugee crisis in the context of the EU’s current response and future options.